Shear strength assessment of reinforced concrete components containing EAF steel slag aggregates. (1st April 2022) - Santamaría, Amaia; Romera, Jesús María; Marcos, Ignacio; Revilla-Cuesta, Víctor; Ortega-López, Vanesa
Abstract: Electric Arc Furnace (EAF) slag can be reused as aggregate in Portland cement concrete mixes. The addition of EAFS and other waste co-products (fly ash, blast furnace slag) will modify the binding properties and will, importantly, enhance the global sustainability of such concretes. These mix designs offer acceptable pumpability and self-compaction in the fresh state and can be reinforced with fibers. In this study, eight different concrete mixes are designed within the range of medium-strength concretes (30–50 MPa) and are characterized in both the fresh and the hardened state. Large concrete volumes are used to pour reinforced beams, which are then subjected to small-span high-load tests to evaluate their resistance to shear stress, by analyzing two types of transversal (shear) reinforcement. The tests yielded promising results, contributing additional evidence on the viability of using recycled EAFS aggregate in structural applications. The mechanical behavior of these concretes was closely correlated with the strength predictions calculated with the formulas listed in various international standards. Graphical abstract: Image 1 Highlights: Eight concrete mixtures manufactured with EAFS, fibers and SCM. Evaluation of fresh (self-compacting and pumpable) and hardened properties. Shear strength testing on eight beams manufactured with sustainable concretes. Effect of the fibers, concrete quality, and reinforcement on the beams shear strength. Experimental shear strength values versus standard's estimated values.